2012
DOI: 10.3389/fpsyt.2012.00093
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects of tDCS on the μ-Opioid System of a Chronic Pain Patient

Abstract: We developed a unique protocol where transcranial direct current stimulation (tDCS) of the motor cortex is performed during positron emission tomography (PET) scan using a μ-opioid receptor (μOR) selective radiotracer, [11C]carfentanil. This is one of the most important central neuromechanisms associated with pain perception and regulation. We measured μOR non-displaceable binding potential (μOR BPND) in a trigeminal neuropathic pain patient (TNP) without creating artifacts, or posing risks to the patient (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
106
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 36 publications
2
106
1
1
Order By: Relevance
“…Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique capable of modifying neuronal resting membrane potential and the level of spontaneous neuronal firing in the area of stimulation as well as in interconnected neural networks 1 including the endogenous μ-opioid system 2 , thereby modulating cortical excitability. The neuromodulatory effects of tDCS, combined with its low cost, simple application and portability, have led to its extensive use over the past decade in a wide variety of settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcranial direct current stimulation (tDCS) is a noninvasive brain stimulation technique capable of modifying neuronal resting membrane potential and the level of spontaneous neuronal firing in the area of stimulation as well as in interconnected neural networks 1 including the endogenous μ-opioid system 2 , thereby modulating cortical excitability. The neuromodulatory effects of tDCS, combined with its low cost, simple application and portability, have led to its extensive use over the past decade in a wide variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…These have included neurophysiological studies, cognitive and behavioral interventions and patient studies assessing disorders such as chronic pain, depression, migraine, stroke, Parkinson's disease and tinnitus 3 . However, delivery of direct current (DC) is performed using large pads, most commonly between 25-35 cm 2 , which stimulate relatively broad areas of cerebral cortex located between the anode and cathode 4 . Therefore, focal stimulation of target cortical regions, not involving stimulation of neighboring anatomical areas, is difficult to achieve with this technique.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed the single active tDCS decreased μ-opioid receptor non-displaceable binding potential levels in (sub) cortical pain-matrix structures compared to sham tDCS, including nucleus accumbens, anterior cingulate cortex, insula, and especially in the posterior thalamus suggesting that the analgesic effect of M1-tDCS is possibly due to direct increase in endogenous opioid release. They also suggested that a single tDCS session may often have subclinical effects, but that repetitive sessions may be necessary to revert ingrained neuroplastic changes related to the chronic pain [36].…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Finally, DosSantos et al identified μ-opioidergic effects of anodal tDCS by positron emission tomography (PET) [36]. They performed 2 mA anodal tDCS for 20 min in one trigeminal NP patient during PET scan using a μ-opioid receptor (μOR) selective radiotracer, [ 11 C] carfentanil.…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Transcranial direct current stimulation (tDCS) is a non-invasive technique that has emerged as a promising treatment for several pain syndromes [1][2][3] . This technique consists in the applying of a weak, direct, constant and low intensity electric current.…”
mentioning
confidence: 99%